2023
DOI: 10.3389/fpls.2022.1040520
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth, salt removal capacity, and forage nutritive value of the annual euhalophyte Suaeda salsa irrigated with saline water

Abstract: Sustainable agricultural development in semiarid and arid regions is severely restricted by soil and water salinization. Cultivation of the representative halophyte Suaeda salsa, which can be irrigated with saline water and cultivated on saline soils, is considered to be a potential solution to the issues of freshwater scarcity, soil salinization, and fodder shortage. However, the salt removal capacity and differences in the forage nutritive value of S. salsa under different saline water treatments remain unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Euhalophytes are plants that can tolerate high levels of salinity and often display tissue succulence as a visible trait [ 12 ]. Research has found that the succulence of S. salsa leaves increases with increasing salt concentrations [ 24 ] and that there is a linear correlation between the succulence of euhalophytes ( Salicornia europaea , S. salsa ) and the dry mass of the shoot [ 32 ]. This suggests that it is possible to use the degree of tissue succulence as an indication of plant growth under salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Euhalophytes are plants that can tolerate high levels of salinity and often display tissue succulence as a visible trait [ 12 ]. Research has found that the succulence of S. salsa leaves increases with increasing salt concentrations [ 24 ] and that there is a linear correlation between the succulence of euhalophytes ( Salicornia europaea , S. salsa ) and the dry mass of the shoot [ 32 ]. This suggests that it is possible to use the degree of tissue succulence as an indication of plant growth under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies showed that the aboveground biomass of S. salsa had a “curvilinear” growth trend as the salt dosage increased, with the highest biomass at 20 g·L −1 . In addition, the succulence of S. salsa leaves increased significantly with increasing salt dosage [ 24 ]. Thus, our results suggest that the degree of tissue succulence does not accurately reflect the growth state of halophytes under salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salt absorption capacity of S. salsa was determined usingthe following Formula (5) ( Wang et al., 2022 ):…”
Section: Methodsmentioning
confidence: 99%
“…Harvesting these parts can help improve the quality of saline–alkali land ( Liang and Shi, 2021 ). Moreover, S. salsa can be used as livestock feed ( Wang et al., 2022 ). Therefore, the utilization of S. salsa as feed can drive the large-scale development and use of saline–alkali lands ( Zhang et al., 2005 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%